Cognitive impulsivity and the development of delinquency from late childhood to early adulthood: Moderating effects of parenting behavior and peer relationships. (6th May 2015) - Menting, Barbara; Van Lier, Pol A. C.; Koot, Hans M.; Pardini, Dustin; Loeber, Rolf
Abstract: Cognitive impulsivity may increase children's risk of developing delinquent behavior. However, the influence of cognitive impulsivity may depend on social environmental risk factors. This study examined the moderating effect of late childhood parenting behaviors and peer relations on the influence of children's cognitive impulsivity on delinquency development across adolescence and early adulthood, while taking possible interactions with intelligence also into account. Delinquent behavior of 412 boys from the Pittsburgh Youth Study was measured annually from ages 13 to 29 years with official arrest records. Cognitive impulsivity (neurocognitive test scores) and intelligence were assessed at age 12–13. Parenting behaviors (persistence of discipline, positive reinforcement, and parental knowledge), peer delinquency, and peer conventional activities were assessed between ages 10 and 13 years. Results showed that, while controlling for intelligence, the influence of youths' cognitive impulsivity on delinquency depended on their parents' behaviors. An interaction was found among cognitive impulsivity, intelligence, and peer delinquency, but instead of cognitive impulsivity, the effect of intelligence on delinquency was particularly moderated. Overall, findings suggest that when there was moderation, high cognitive impulsivity and low intelligence were associated with an increased probability for engaging in delinquency predominantly among boys in a good social environment, but not in a poor social environment.